2019
DOI: 10.1016/j.surfcoat.2019.125063
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-nanodiamond coatings electrodeposited from tartrate electrolyte at ambient temperature

Abstract: In this study, nanocrystalline Ni and Ni-diamond coatings were obtained by electrodeposition from tartrate electrolyte at ambient temperature to achieve good corrosion and wear resistance. Microhardness and adhesion tests respectively were performed for the wear resistance determination. Electrochemical impedance spectroscopy and linear polarization methods were used for corrosion resistance measurements and atomic force microscopy, and scanning electron microscopy were used for surface property characterizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 43 publications
0
29
0
1
Order By: Relevance
“…However, a slight increase in the crystallite size of the coatings deposited in mode 1 and mode 2 can be also explained by the addition of TiO 2 . In this case, the second-phase particles may increase the number of structural defects, leading to an increase in the grain size [13] , [68] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a slight increase in the crystallite size of the coatings deposited in mode 1 and mode 2 can be also explained by the addition of TiO 2 . In this case, the second-phase particles may increase the number of structural defects, leading to an increase in the grain size [13] , [68] .…”
Section: Resultsmentioning
confidence: 99%
“…Electrodeposition allows for the controlled incorporation of the second phase particles into the metal matrix, thus such composite coatings are usually characterized by improved microhardness, functional properties, wear- and corrosion resistance, which extends their potential applications [7] , [8] , [9] , [10] , [11] , [12] . In this regard, electrodeposition attracts more and more attention in the fabrication of novel types of alloys and nanocomposites [13] , [14] , [15] , [16] , [17] , [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al [18] studied the high-particle-content Ni/diamond coating and proved that the particle content was effectively enhanced employing two-step electrophoretic and electrodeposition means, resulting in an effective improvement in wear resistance. Makarova et al [19] electrodeposited nickel-nanodiamond coatings from tartrate electrolyte and reported that the addition of 5 g L –1 nanodiamonds could strengthen the microhardness, wear resistance, and corrosion resistance. Almost all scholars believe that the diamond incorporations can perfect the abrasion and corrosion performance of the Ni coatings [20] .…”
Section: Introductionmentioning
confidence: 99%
“…These widespread properties reflect commercial importance of traditional nickel coatings and their versatility in technical and decorative applications. Nickel is used often as a matrix for electrochemical synthesis of composite coatings [4][5][6]. They can contain a variety of hard or soft nano-or microsized particles improving physio-chemical properties of the metallic layers.…”
Section: Introductionmentioning
confidence: 99%